Sustainable remote and rural eco-tourism: Applying a systemic, holistic, a interdisciplinary and participatory (Ship) approach - Siang, Ting Siew; W. , Alvin Yeo; C.L. , John Phoa; May, Chiun Lo; Kulathuramaiyer, Narayanan; Nair, Vikneswaran (2013)
Long Lamai is a remote and rural Penan community in the interiors of Borneo in Sarawak, Malaysia. It is only accessible by either an 8-hour 4- wheel-drive on the logging road or an hour's flight via a 19-seater Twin Otter, and then a mandatory hour's river ride upriver. Long Lamai is being developed as an eco-tourism site, given the existence of natural attractions such as untouched flora and fauna, and the unique Penan's culture. A telecentre (which provides computing facilities and Internet connection via a satellite system, and using solar-power), was established in 2009. The management committee, which is running the telecentre, is also spearheading the use of ICTs in establishing Long Lamai as a tourist attraction and hence, to improve the socio-economic status. In addition to this, there are many aspects which need to be addressed, for example, the issues of environment, e-commerce, handicraft development, transportation, sourcing of food, sourcing of raw materials for the handicrafts, tour guiding, and development of tourism activities. One approach to the design and development of sustainable eco-tourism industry is by viewing the whole socio-economic transformation process as a complex system. The complex system comprises the various "sub-systems" such as those described above, e.g. environment, e-commerce, and handicraft development. All these subsystems interact and affect each other, and has to work effectively and efficiently together. To understand this complex system, we take the SHIP (systemic, holistic, interdisciplinary and participatory) approach. This paper thus details a study of Long Lamai as an eco-tourism site from the SHIP perspective.